Pigeon Fever in Florida Horses - Sally DeNotta; Amanda House (EDIS, 2023)
This article provides an overview of Pigeon Fever in horses, an infectious condition caused by Corynebacterium pseudotuberculosis. C. pseudotuberculosis is a gram-positive, rod-shaped bacteria that can survive for weeks to months (or possibly even years) in the soil. While horses, cattle, and goats can all be infected with C. pseudotuberculosis, they are typically infected with different strains of the bacteria, and transmission between species is not thought to occur. Horses with pigeon fever develop large, painful abscesses in their muscles. There is a propensity for abscesses to develop in the pectoral muscles, giving the horse a “pigeon breasted” appearance, hence the name pigeon fever. It is important to note that birds are not involved in the transmission or pathogenesis of this condition. In Florida, the largest number of pigeon fever cases are typically reported in the dry months of fall and winter. In goats, the disease is known as “Caseous Lymphadenitis”, and affected animals develop abscesses in lymph nodes and under the skin (typically on the head, behind the ears, or on the neck, shoulder or flank).